2022
DOI: 10.3168/jds.2022-22154
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of the changes in Johne's disease management practices on Ontario dairy farms through repeat risk assessment

Abstract: Johne's disease (JD) control is often based on the culling of positive animals and the adoption of management practices that minimize exposure of calves to the pathogen Mycobacterium avium ssp. paratuberculosis (MAP). From 2010 to 2013, Ontario, Canada, instituted a voluntary Johne's control program consisting of whole-herd testing and a Risk Assessment and Management Plan (RAMP). The RAMP consisted of 38 questions that evaluated 5 different management areas to characterize herd risk for MAP introduction and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Purchasing of cattle from infected herds or infected individuals is one of the main risk factors for JD transmission between herds 18 . In Ireland, studies have shown that approximately 60%–80% of dairy herds purchase cattle to bring into the herd, 18,19 comparable to the data (89.4%) from this study, which shows that herds that report no animal introductions are a minority 20 . Due to the lack of JD test information available at time of purchase, farmers are likely to purchase high or unknown JD risk animals and then manage risk of onward JD spread through quarterly milk testing.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Purchasing of cattle from infected herds or infected individuals is one of the main risk factors for JD transmission between herds 18 . In Ireland, studies have shown that approximately 60%–80% of dairy herds purchase cattle to bring into the herd, 18,19 comparable to the data (89.4%) from this study, which shows that herds that report no animal introductions are a minority 20 . Due to the lack of JD test information available at time of purchase, farmers are likely to purchase high or unknown JD risk animals and then manage risk of onward JD spread through quarterly milk testing.…”
Section: Discussionsupporting
confidence: 78%
“… 18 In Ireland, studies have shown that approximately 60%–80% of dairy herds purchase cattle to bring into the herd, 18 , 19 comparable to the data (89.4%) from this study, which shows that herds that report no animal introductions are a minority. 20 Due to the lack of JD test information available at time of purchase, farmers are likely to purchase high or unknown JD risk animals and then manage risk of onward JD spread through quarterly milk testing. Multivariate logistical regression analysis of the VRAMP data found that farmers were significantly more likely to have identified a suspected case of JD within the herd if they had kept one or more purchased animals for breeding.…”
Section: Discussionmentioning
confidence: 99%